Madeleine L'Engle's A wrinkle in time : the graphic novel - Larson, Hope (Square Fish, 2015)
A graphic novel adaptation of the classic tale in which Meg Murry and her friends become involved with unearthly strangers and a search for Meg's father, who has disappeared while engaged in secret work for the government.